Can lack of physical activity cause kidney function problems? A Cross-Sectional Study in Kendari City - Tasnim, Tasnim; Sugireng, Sugireng; Imran, Imran; Akib, Nur Illiyyin (YCAB Publisher, 2025)
Background: chronic kidney disease (CKD) is often undetected until reaching advanced stages, posing a serious public health concern. In Kendari City, Indonesia, lifestyle shifts and increased sedentary behaviour have raised concerns about rising CKD prevalence. Physical inactivity is suspected to be a modifiable risk factor, but local empirical data remain limited. Objective: This study aimed to investigate the association between physical activity levels and early kidney function decline, as indicated by urine protein concentration, among adults in Kendari City, Southeast Sulawesi. Methods: A cross-sectional quantitative study was conducted from June to August 2023, involving 119 adults aged 17–75 years selected through purposive sampling across three urban sub-districts. Physical activity was assessed using the International Physical Activity Questionnaire–Short Form (IPAQ-SF) and categorized into low (<600 METs/week), moderate (600–2999), and high (≥3000). Kidney function was measured through morning urine protein dipstick tests and classified into normal, low, moderate, or severe proteinuria. Data were analysed using chi-square, linear regression, and multinomial logistic regression tests. Results: The average physical activity level was 1560.37 ± 1516.78 METs/week (moderate), and the mean urine protein level was 0.64 ± 1.08 g/L (low risk). A statistically significant inverse relationship was found between physical activity and urine protein levels (p < 0.001; β = -0.394). Participants with high physical activity had 100% normal proteinuria, while those with low activity had the highest rates of moderate (32.6%) and severe (30.4%) proteinuria. Multinomial regression indicated that individuals with high activity were 27 million times more likely to have normal protein levels compared to those with low activity (p < 0.001), suggesting a strong protective effect. Conclusion: Lower physical activity is significantly associated with increased risk of impaired kidney function in urban adults. Public health strategies should prioritize structured physical activity promotion and early screening to prevent CKD progression in Kendari City. Further research is needed to examine other contributing factors such as diet, hydration, and lifestyle behaviours.